2015
DOI: 10.1093/infdis/jiv147
|View full text |Cite
|
Sign up to set email alerts
|

Structural Bone Deficits in HIV/HCV-Coinfected, HCV-Monoinfected, and HIV-Monoinfected Women

Abstract: Background. Coinfection with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) is associated with reduced bone mineral density (BMD) and increased fracture rates, particularly in women. The structural underpinnings for skeletal fragility in coinfected women have not been characterized. We used tibial peripheral quantitative computed tomography to evaluate skeletal parameters in women, by HIV/HCV status.Methods. We conducted a cross-sectional study among 50 HIV/HCV-coinfected, 51 HCV-monoinfected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…29 A separate analysis among HIV/HCV-coinfected patients in the Swiss HIV Cohort Study found that deferring treatment from METAVIR stage F2 until stage F3 or F4 increased the risk of liver-related death 2-fold and 5-fold, respectively. 30 Denial of DAA treatment can also lead to ongoing HCV-associated inflammation, which might increase the risk of extra-hepatic complications, including bone, 31,32 kidney, 33,34 cardiovascular, 35 and neuropsychiatric disease. 36 Further, failure to treat and cure chronic HCV can lead to continued risk of HCV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…29 A separate analysis among HIV/HCV-coinfected patients in the Swiss HIV Cohort Study found that deferring treatment from METAVIR stage F2 until stage F3 or F4 increased the risk of liver-related death 2-fold and 5-fold, respectively. 30 Denial of DAA treatment can also lead to ongoing HCV-associated inflammation, which might increase the risk of extra-hepatic complications, including bone, 31,32 kidney, 33,34 cardiovascular, 35 and neuropsychiatric disease. 36 Further, failure to treat and cure chronic HCV can lead to continued risk of HCV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…reported reduced trabecular bone density and trabecular and cortical thickness in both the radius and tibia in 30 young American African and Hispanic men; reduced bone stiffness was also demonstrated at these sites using finite element analysis . Finally, women co‐infected with HCV/HIV have been shown to have significantly lower trabecular volumetric BMD and smaller cortical dimensions in the tibia, compared to healthy subjects . In all these studies, the majority of subjects were established on ART, and whether the observed changes reflect bone loss during initiation of therapy is unclear.…”
Section: Mechanisms Of Bone Fragility and Fracture In Hiv Infection (mentioning
confidence: 99%
“…As mentioned above, although not associated with significantly lower BMD than HIV or HCV mono-infection in most studies [27,31,32,57,58], HIV/HCV co-infection has been consistently shown to predict much greater fracture risk than HIV mono-infection (hazard ratios ranging from 1.2 to 2.4) [2,6,8]. This suggests that BMD might be inadequately assessing fracture risk in this population.…”
Section: Introductionmentioning
confidence: 96%
“…Among HIV-infected patients, BMD further decreases 2–6% over the first two years of antiretroviral therapy (ART) initiation [2325]. HCV coinfection has been associated with further reductions in BMD among HIV-infected patients in some [26–30], but not all studies [3033]. These findings raise the possibility that the higher fracture risk observed in patients with chronic HCV infection might not be due to low BMD alone, but could involve other mechanism(s).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation